Pengaruh Brand Experience dan Brand Loyalty terhadap Brand Equity Produk Apple dengan Perceived Quality sebagai Variabel Intervening - Amanta, Aulia Putri; Nopitasari, Dwi; Martiza, Pingkan Viola (LANCAH: Jurnal Inovasi dan Tren, 2024)
The aim of this study is to identify the relationship between Brand Experience and Brand Loyalty on Brand Equity for Apple products in Sukoharjo Regency. The sample used in this study consists of 174 respondents residing in Sukoharjo Regency who have used and own Apple products. The data collection method in this study employed a questionnaire. Data were analyzed using SmartPLS. The hypotheses in this study indicate that Brand Experience has a significant influence on Brand Loyalty, Brand Equity, and Perceived Quality. Additionally, Brand Loyalty also has a significant influence on Brand Equity and Perceived Quality. Moreover, Perceived Quality has a significant influence on Brand Equity.